Comparison of cryogenic flow boiling in liquid nitrogen and liquid hydrogen chilldown experiments. (September 2015) - Hartwig, Jason; Hu, Hong; Styborski, Jeremy; Chung, J.N.
Highlights: Quenching characteristics are compared between two cryogens. Flow visualization clips. Liquid hydrogen exhibits annular flow at low inlet subcooling and high mass flux. Liquid nitrogen exhibits inverted annular flow at low inlet subcooling and low mass flux. Abstract: This paper presents a comparison between experimental results from recent liquid hydrogen (LH2 ) transfer line chilldown experiments at high Reynolds (Re) numbers versus liquid nitrogen (LN2 ) experiments conducted at low Re numbers. Parasitic heat leak, inner wall temperatures, inner wall heat fluxes, and heat transfer coefficients are computed to compare between the two systems. Analysis of temperature traces and flow visualization indicates that the chilldown process evolves much more rapidly at higher Re numbers due to a quick transition from vapor flow to annular liquid flow and near immediate liquid contact along the pipe walls. The lower kinematic viscosity and surface tension of LH2, along with reduced parasitic heat leak and higher Re numbers relative to the LN2 experiments, causes chilldown to proceed almost immediately into the nucleate boiling regime, in comparison to low Re flows where >75% of the chilldown is spent in vapor film boiling.